Ps-H scattering using the three-state positronium close-coupling approximation - Sinha, P. K.; Chaudhury, P.; Ghosh, A. S. (Iop Publishing Ltd, 1997)
Positronium scattering off a hydrogen target has been studied employing a three-state positronium model close-coupling approximation (CCA) with and without electron exchange. Elastic, excitation and quenching cross sections are reported at low and medium energies. The effect of electron exchange is found to be significant at low energies. The ratio of quenching to the total cross section (the conversion ratio) approaches the value of 0.25 with increase of energy, as expected.